SUMMARY REPORT OF PORTABLE SYSTEM OPERATIONS FOR PROJECT LONG SHOT. - GEOTECH GARLAND TX (1966)
In October 1965, Teledyne Industries, Geotech Division, was assigned to occupy five portable system sites in Northern Canada and one portable system site in Greenland to record seismic data from the Project LONG SHOT detonation. The six portable seismographs successfully recorded data for approximately two weeks preceding and two weeks following the LONG SHOT detonation. The results of the portable system operations for Project LONG SHOT indicate that the portable seismograph systems are an effective means of recording seismic data for short periods of time in remote locations. This effectiveness is expected to be increased as the system operators become more familiar with the instrumentation. (Author)